The Ethics of Interrogation - Paul Lauritzen (Georgetown University Press, 2013)
Toward the end of his book Democracy and Tradition, Jeffrey Stout argues that the virtues necessary to sustain traditions of democratic practice in the United States will be sorely tested in the coming years by the struggle against terrorism. Fear and resentment are the enemy of critical self-reflection, and democracy cannot flourish where self-reflection and the virtues that sustain such scrutiny are absent. Yet terrorism is designed precisely to induce fear, and fear can paralyze thought. I agree with Stout on this point, as well as with his contention that we had better be prepared to demand from our leaders and our fellow citizens reasons for actions taken in the â€œwarâ€ against terror, if we are to have any hope of prevailing in this struggle.1 Fear not only paralyzes thought; it breeds violence and division. This volume takes seriously Stoutâ€™s argument that democracy is a tradition in which asking for and being prepared to give ethical reasons for our own and each otherâ€™s actions is central. You may know a prophet by his fruits, but you will know a democrat by how he reasons in addition to how he behaves. How, then, are Americans doing in critically engaging terrorism with the resources of democracy? In raising this question, I am not asking how the US military is faring in Iraq or Afghanistan. Nor am I questioning how, say, the Department of Homeland Security is doing in preparing to deal with terrorist attacks. Instead, I am asking about something more amorphous, but no less important. How are citizens thinking and reasoning about the struggle against terrorism, and how is this reasoning manifest in their actions?